Conflict and insecurity: A sociological perspective on perceptions of insecurity in conflict-affected Democratic Republic of Congo. (May 2017) - Van der Bracht, Koen; Flaam, Hélène; Vlassenroot, Koen; Van de Putte, Bart
This article focuses on insecurity perceptions in conflict-affected areas. The authors apply sociological theories on the determinants of perceived security risks and test hypotheses concerning theories on social and physical vulnerability, social disorder and social integration in the area where the Lord's Resistance Army (LRA) has operated. The study uses data from a survey conducted in 2013 in the territory of Faradje (Haut-Uele) and applies multilevel models to 443 individuals living within 21 different villages and internally displaced persons (IDP) camps. The results indicate that insecurity perceptions and fear of attacks are still widespread, causing individuals to adapt their behaviour and IDPs to refrain from returning home. These concerns are unaffected by social and physical vulnerabilities. The study finds a positive significant effect of the presence of IDPs in the villages and IDP camps on insecurity perceptions. This suggests possible effects of social disorder and a lack of social integration due to the arrival of IDPs in the area. Although improving the security situation itself is an important factor, this article shows that addressing insecurity perceptions might be an important factor as well.